Uptake and continuation rates of the intrauterine system in a university student general practice population in the UK. Issue 3 (14th December 2012) - Armitage, Catherine Marie; Mitchell, Carolyn; Wigan, Caroline; Smith, Debbie A
Abstract : Objective: To follow a series of 100 women attending for fitting of the levonorgestrel-releasing intrauterine system (LNG IUS) registered at a single urban general practice serving the students of the local universities and higher education colleges. Methods: This was a prospective observational study. A questionnaire was completed by the fitter in discussion with the patient at the time of attendance for IUS fitting. Follow up was by telephone at 6 weeks, 6 months and 9–12 months after fitting. Results: The age range of women within the series was 18–38 years. 97 women were nulliparous. 37 women selected the IUS as their preferred method of contraception. 12 women chose the IUS primarily for non-contraceptive reasons. 75 women still had the IUS at 12 months' follow up with 11 lost to follow up at this point. No pregnancies or perforations were reported. Conclusions: The IUS is an acceptable form of contraception in young women, including nulliparous women, and should be offered alongside other methods as first line without restriction when offering contraceptive options to this age group.